2020
DOI: 10.1177/8755123320943985
|View full text |Cite
|
Sign up to set email alerts
|

Research to Resource: Developing a Sense of Community in Online Learning Environments

Abstract: Many music educators are concerned about building healthy classroom communities as they prepare to transition to online or blended learning environments. Research involving distance education has indicated that several techniques in the design and delivery of online instruction can increase students’ sense of community, commitment to the course, and overall learning experience. The purpose of this research-to-resource article is to provide music educators with research-based strategies for establishing and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example, Shackelford and Maxwell (2012) found that the interactions such as collaborative group projects, exchanging resources, and sharing of personal experiences predicted a sense of community in an online graduate course of almost 400 students (78% female). Adams (2021) suggests student collaboration as a means of encouraging a sense of community among students. Similarly, pre-pandemic researchers found that the use of peer groups…”
Section: Sense Of Communitymentioning
confidence: 99%
“…For example, Shackelford and Maxwell (2012) found that the interactions such as collaborative group projects, exchanging resources, and sharing of personal experiences predicted a sense of community in an online graduate course of almost 400 students (78% female). Adams (2021) suggests student collaboration as a means of encouraging a sense of community among students. Similarly, pre-pandemic researchers found that the use of peer groups…”
Section: Sense Of Communitymentioning
confidence: 99%
“…In an asynchronous course, educators might consider providing optional synchronous class meetings to allow students the opportunity to interact. If attendance is optional, the teacher can post a recording of the session for those who cannot attend [15]. Technological innovation has given multimedia support to the teaching faculty, changing how they interact with students, particularly with students who work, who are engaged in family needs, who live in rural areas or are far from an educational institution [16].…”
Section: B Digital Literacy Practicesmentioning
confidence: 99%
“…Supplemental learning materials have become increasingly common in education as educators and parents seek to provide students with more personalized and engaging learning experiences [1].…”
Section: Introductionmentioning
confidence: 99%